2015
DOI: 10.1097/hpc.0000000000000047
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Red Blood Cell Distribution Width and Mortality of Patients with Acute Myocardial Infarction Referring to Tehran Heart Center

Abstract: Six-month mortality was significantly higher in patients with MI with high RDW. Thus given that RDW is an inexpensive and available laboratory test, it could be used for mortality risk assessment and follow up the patients for stricter control of other modifiable risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The prognostic value of RDW for short-term or long-term cardiovascular events have been demonstrated in STEMI patients [ 20 , 25 ]. In a meta-analysis involving 80216 patients from 22 studies, RDW was a remarkably strong predictor of all-cause mortality (HR = 1.80, 95% CI:1.35–2.41, P < 0.001) and non-fatal adverse events (HR = 1.86, 95% CI:1.50–2.31, P < 0.001), although there was significant heterogeneity in the different studies [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic value of RDW for short-term or long-term cardiovascular events have been demonstrated in STEMI patients [ 20 , 25 ]. In a meta-analysis involving 80216 patients from 22 studies, RDW was a remarkably strong predictor of all-cause mortality (HR = 1.80, 95% CI:1.35–2.41, P < 0.001) and non-fatal adverse events (HR = 1.86, 95% CI:1.50–2.31, P < 0.001), although there was significant heterogeneity in the different studies [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…[3637] Although the relationship between RBC count and cardiovascular diseases remains unclear, a strong relationship between RDW and cardiovascular diseases has been demonstrated in several studies. [34383940] In a previously conducted study, increased RDW and RBC count was reported in patients with depression, which improved after successful treatment with antidepressants. [41]…”
Section: Discussionmentioning
confidence: 99%
“…However, most of these studies were all limited by the relatively small sample size and did not include all stroke populations but only included ischemic stroke or SAH. Additionally, present reports had indicated that RDW is related to the prognosis of patients with AMI or acute coronary syndrome ( 21 – 25 ), but these studies had not clearly clarified the effect of the comorbidities on the relationship between RDW and death in patients with stroke. In contrast, there were two previous studies that had pointed out opposite results with ours as follows.…”
Section: Discussionmentioning
confidence: 92%